Obesity, Liberty, and Public Health Emergencies - Herington, Jonathan (The Hastings Center report, 2014)
Widespread obesity poses a serious challenge to health outcomes in the developed world and is a growing problem in the developing world. There has been a raft of proposals to combat the challenge of obesity, including restrictions on the nature of food advertising, the content of prepared meals, and the size of sodas; taxes on saturated fat and on calories; and mandated “healthy-options” on restaurant menus. Many of these interventions seem to have a greater impact on rates of obesity than does simply providing information about health risks and healthier lifestyles. The more interventionist policy options have, however, been implemented only slowly, in large part because of criticisms that they are unjustified infringements on the liberty of consumers. Food industry groups, free-market think tanks, and the popular press regard measures that incentivize or penalize particular food and lifestyle choices as unjustifiable state regulation of purely self-regarding behavior. To counteract the liberty-oriented position, those who favor a more interventionist role for the state have recently argued for labeling obesity as a public health emergency. By labeling obesity as a public health emergency, policy-makers could override concerns about individual liberty in order to pursue more interventionist policies designed to guide consumer choices toward healthier lifestyles. In this paper, we argue that, contrary to initial appearances, obesity possesses some of the morally relevant features of public health emergencies, though we do not argue that it actually constitutes one.